(untitled) (Journal of Medicine, 2024)
Background: Increased resistance to fluoroquinolones has been observed in members of the Enterobacteriaceae, including Proteus species. The extensive use of fluoroquinolones and the presence of plasmid-mediated quinolone resistance (PMQR) genes are believed to contribute significantly to fluoroquinolone resistance. This study highlights the prevalence of ciprofloxacin-resistant Proteus species and the presence of specific PMQR genes among them, emphasizing their potential role in quinolone resistance. Method: The study included 30 ciprofloxacin-resistant Proteus isolates collected from wound swab, pus, urine, and blood samples. Identification of Proteus species was performed using culture and biochemical tests. Antibiotic susceptibility test was conducted using the Kirbey-Bauer disc-diffusion method. The minimum inhibitory concentration (MIC) of ciprofloxacin among ciprofloxacin-resistant Proteus species was determined using the agar dilution method. The study aimed to detect specific PMQR genes, namely aac(6´) lb-cr, qnrA, qnrB, qnrD, and qnrS, using polymerase chain reaction (PCR). Result: A total of 42 Proteus species were isolated from 310 various samples. Among the Proteus isolates, 71.43% were ciprofloxacin resistant. The study found that 30% of ciprofloxacin-resistant isolates were positive for aac(6´) lb-cr gene, 13.33% for qnrA and qnrS respectively and 10% for qnrD gene. In total, 60% of ciprofloxacin-resistant Proteus isolates were positive for at least one PMQR gene. The qnrB gene was not detected among ciprofloxacin-resistant Proteus species. The MIC of ciprofloxacin ranged from 8 μg/ml to 128 μg/ml among ciprofloxacin-resistant Proteus isolates. Conclusion: This study suggests aac(6´) lb-cr, qnrA, qnrS, and qnrD genes are emerging in Proteus species, potentially contributing to the development of quinolone resistance and has implications for clinical management and public health. J MEDICINE 2024; 25: 149-154